Attitudes towards vaccination against COVID-19 among athletes of Russian national teams in comparison with non-athletes aged 18 to 40 - A. V. Vasileva; T. A. Karavaeva; D. S. Radionov; A. V. Yakovlev; S. I. Barshak; K. S. Nazarov; A. V. Zholinskiy; B. A. Polyaev; I. N. Mitin (National Electronic Information Consortium (NEICON), 2023)
The purpose of this work was to study the attitude of the Russian population to vaccination against COVID-19. Vaccination attitudes in young adults were studied both in the general population and among those who are professionally involved in sports, since attitudes towards health and the initial level of physical resources are important for forming attitudes towards vaccination. A total of 2579 people aged 18 to 40 were examined. Of these, 2233 are from the general population, 346 are high performance athletes.Methods. This was a cohort cross-sectional study. A specially designed questionnaire was used, located on Internet resources 2 months after the start of mass vaccination in Russia.Results. In the group of elite athletes, there are significantly more people who consider vaccination unnecessary or treat it indifferently, and a smaller proportion of those who consider it useful or doubt its effectiveness as compared to the general population of the same age. Low adherence to vaccination may be associated with fear of potential complications. Among elite athletes, there are significantly more people who are seriously afraid of complications from vaccination - 143 (41.3 %), compared to the first group of respondents - 745 (33.4 %) (p < 0.01, φ = 2.839). Probably, these concerns are related to the crucial importance of health and physical condition for professional athletes.Conclusions. It is advisable to develop recommendations for vaccination against COVID-19 for elite athletes, which will describe in detail the benefits of vaccination for athletes, possible side effects, their frequency and impact on the training process.